Tadribat to Enhance the Nahwu Competence of Arabic Language Education Students at UIN Sulthan Thaha Saifuddin Jambi - Ni'mah, Izzah Naelun; Musli, Musli (Universitas Muhammadiyah Yogyakarta, 2023)
This study seeks to elucidate initiatives aimed at enhancing students' comprehension of nahwu rules using tadribat. Despite the development of Arabic in Indonesia, the process of acquiring the language has encountered persistent challenges. One aspect is the mastery of nahwu throughout the learning process. This study is qualitative, specifically aimed at gathering information via field research. The employed methodology is naturalistic. This study focused on the students of the Arabic language education class of 2021, while the research examined the students' endeavors to comprehend Nahwu rules through Tadribat Arabic Language Education. At UIN Sulthan Thaha Saifuddin Jambi, the data collection methods employed were observation, interviews, and documentation. The analytical procedures include data reduction, data display, and data verification. The findings of this study are 1) Student Endeavors in Comprehending Nahwu Regulations Through the Student Tadribat Class of 2021 Arabic language instruction at UIN Sulthan Thaha Saifuddin Jambi involves the study of Nahwu rules through exercises provided by instructors, specifically focusing on maharatul i'tuma' (reading skills), maharatul kalam (speaking skills), maharatul qiro'ah (reading skills), and maharatul kitabah (writing abilities). Enhancing Students' Proficiency in Comprehending Nahwu Principles via the Tadribat Class of 2021 Arabic Language Education The number of students at UIN Sulthan Thaha Saifuddin Jambi remains low due to insufficient passion for studying nahwu and a lack of self-motivation to utilize available time, such as using their free time to learn nahwu regulations.